Vehicle Fuel Economy Improvement through Vehicle Optimization in 1-D Simulation Cycle towards Energy Efficient Vehicle (EEV) - Zainal Abidin, Shaiful Fadzil; Khalid, Amir; Shafai@Shafie, Siti Nor Zulaikha; Zahari, Izzarief; Abdul Jalal, Rifqi Irzuan (International Journal of Integrated Engineering, 2020)
The high average of fuel consumption in vehicle for ASEAN countries compared to global average has led to the establishment of Energy Efficient Vehicle (EEV) by National Automotive Policy (NAP) 2014. PROTON Saga 1.3L 4-speed automatic transmission (4AT) with 6.80 L/100km fuel consumption, it is crucial to reduce the fuel consumption in order to fulfil the NAP 14 target which is 6.0 L/100km so that it stays competitive in the market and also to support the ASEAN emission legislation. The objectives of this research are to design and develop a 1-Dimensional 4-AT vehicle model for fuel economy and performance analysis as well as to evaluate and optimize vehicle model to achieve the product target and legislation requirements. The PROTON Saga 1.3L 4-AT vehicle model which is a B-Segment passenger vehicle will be developed using 1-Dimensional simulation software. The correlation between the base vehicle model and actual vehicle model is 0.14% for fuel consumption and 2.22% for 0-100km/h, since the value is less than 4%, the vehicle model can be concluded as valid and authentic. All the data and engine maps used in this research are provided by PROTON Engineering Department to support the accuracy of findings. For each parameter considered in this research, the optimization was performed in simulation where it begins from the current vehicle engine configuration and then applying each parameter at each step until the anticipated configuration of vehicle has achieved. The parameters involved in this research are vehicle weight, aerodynamic, rolling resistance, final gear ratio, and idle speed. Stop start system was used as an advanced alternative way to mitigate the fuel consumption since it is cost consuming. The fuel consumption for an optimized model is 6.01 L/100km with 0.17% difference with the real target which is 6.0 L/100km. The current vehicle model fuel consumption is 6.80 L/100km, thus, it has been successfully reduced to 6.01 L/100km which is equivalent to 11.62% without implementing stop start system and 25.03% with the implementation of stop start system. It seems that the beneficial to examine various possible solution concepts, and to establish understanding on the effectiveness and synergies between powertrain technologies and vehicle design in reducing the overall fuel consumption ad emission.